Sustainable Rice Plant Growth Promotion by Bacteria Isolated from Rhizosphere Soil - Behera, Bikash; Mahto, Kumudini; Awesh Azam, Saikh Md; Mishra, Rashmi Ranjan; Sethi, Bijay Kumar; Pradhan, Biswaranjan; Singh, Santosh Kumar; Hota, Tapaswini; Dey, Harishankar (Jordan Journal of Agricultural Sciences, 2024)
In the present study, sixteen bacterial isolates were collected and identified from the rhizosphere soil of the bean plant (Phaseolus vulgaris), named BB-1 to BB-16. Out of the sixteen bacterial isolates, six isolates showed positive activity of phosphate solubilization ability, three bacterial isolates were found positive for ammonia production, six were positive for Indole acetic acid (IAA) production, three could solubilize potash, three bacterial isolates produced cellulase, six exhibited positive for chitinase, five were tested positive for amylase and four bacterial isolates were positive for protease activity. Hydrogen Cyanide (HCN) production was noticed by the bacterial isolates BB-7only. The fungal pathogen such as Aspergillus terreus, and Penicillium rubidurum was resistant to most bacterial isolates, whereas bacterial isolate BB-3 showed sensitivity against Penicillium rubidurum. Their quantitative phosphate solubilization ability was 47.5-77.8 µg/ml, ammonia production was between 2.45 - 3.45 mg/l, and IAA production was 22.5 -29.5 µg/ml. Of the sixteen bacterial isolates, one bacterial isolate, BB-7, was positive for most of the tests and identified as Pantoea agglomerans. Plant growth-promoting activity of the isolate showed that in comparison to the control rice plant, higher root and shoot growth was achieved in rice pot inoculated with P. agglomerans culture